EFEKTIVITAS NEGOSIASI PENYELESAIAN SENGKETA LINGKUNGAN HIDUP SECARA HUKUM PERDATA DI LUAR PENGADILAN( NON-LITIGASI) DI INDONESIA - Ahmad Ferdian Ramadhani; Apriliana Anggun Triwardani; Lucky Dafira Nugroho (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Environmental disputes are complex problems and require effective and efficient resolution. Negotiation of environmental dispute resolution through civil law outside the court (non-litigation) is an attractive alternative to resolve conflicts without going through a long and expensive trial process. This study aims to analyze the effectiveness of negotiation in resolving environmental disputes through civil law outside the court. This study uses literature study and case analysis methods to understand the negotiation process and its results in resolving environmental disputes. The results of the study indicate that negotiation can be an effective method in resolving environmental disputes, because it can promote good communication between the disputing parties, increase public awareness and participation, and produce more creative and flexible solutions. This study also identifies several factors that influence the effectiveness of negotiation, such as the ability of the negotiator, trust between the disputing parties, and the presence of a neutral facilitator. The results of the study indicate that negotiation can be an effective and efficient alternative in resolving environmental disputes, and can help increase public awareness and participation in protecting the environment.